An immunogenetic view of COVID-19 - Aguiar, Vitor R. C.; Augusto, Danillo G.; Castelli, Erick C. [UNESP]; Hollenbach, Jill A.; Meyer, Diogo; Nunes, Kelly; Petzl-Erler, Maria Luiza (FapUNIFESP (SciELO), 2021)
Meeting the challenges brought by the COVID-19 pandemic requires an interdisciplinary approach. In this context, integrating knowledge of immune function with an understanding of how genetic variation influences the nature of immunity is a key challenge. Immunogenetics can help explain the heterogeneity of susceptibility and protection to the viral infection and disease progression. Here, we review the knowledge developed so far, discussing fundamental genes for triggering the innate and adaptive immune responses associated with a viral infection, especially with the SARS-CoV-2 mechanisms. We emphasize the role of the HLA and KIR genes, discussing what has been uncovered about their role in COVID-19 and addressing methodological challenges of studying these genes. Finally, we comment on questions that arise when studying admixed populations, highlighting the case of Brazil. We argue that the interplay between immunology and an understanding of genetic associations can provide an important contribution to our knowledge of COVID-19.
Keywords: COVID-19; HLA; Immunogenetics; KIR; SARS-CoV-2